Strategi Inovasi Bisnis untuk Meningkatkan Daya Saing dan Pertumbuhan UMKM di Eral Digital 4.0 pada Cafe Laberka Dompu - Afriyanti, Nur; Mansyuri, M. Ikhwan; Sumarni, Sumarni (Indo-Fintech Intellectuals: Journal of Economics and Business, 2025)
The digital era 4.0 has brought significant changes to the business world, including for Micro, Small, and Medium Enterprises (MSMEs). It is a key factor in increasing the competitiveness and growth of MSMEs, especially in the culinary industry such as Cafe Laberka Dompu. This study aims to analyze the business innovation strategy implemented by Cafe Laberka Dompu in facing the challenges of the digital era 4.0. The research approach used is qualitative with a case study method. Data were collected through in-depth interviews, direct observation, and document analysis. The results of the study show that Cafe Laberka Dompu implements various innovation strategies, including digital marketing, utilization of e-commerce platforms, product development based on consumer trends, and improving technology-based services. Supporting factors for the success of business innovation include adaptation to technology, creativity in product development, and customer involvement in the innovation process. This study provides insight for other MSMEs to adopt innovation strategies to increase competitiveness and business growth in the digital era.